PROFIL PENAMBANG EMAS ABAI SANGIR BATANG HARI SOLOK SELATAN - BOBI NASRIANTO; Syafri Anwar (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
The research objective was to determine the profile of the gold miners in Abai Sangir Batang Hari Solok Selatan. This type of research is qualitative research. The data used to complete this research is primary data. Primary data were obtained from direct interviews with the Nagari Abai community, Sangir Batang Hari District, South Solok Regency, gold miners, and Abai community leaders who know the history of mining in Nagari Abai. Data collection techniques in this study used observation, interview, and documentation techniques. Data analysis techniques, namely by way of data reduction, data presentation, and drawing conclusions. The results of this study are: (1) Seen geologically, there is a subduction zone (plate collision) and the location is also a layer of volcanic eruptions, a mixture of these minerals formed crystallization which forms several minerals such as Au (gold) , Ag (silver). ), Cu (copper), Pb (lead), and Zn (zinc). So with the gold there, people use it as a livelihood. (2) Gold mining in Nagari Abai is carried out in two ways, namely conventional and mechanical. Conventionally using conventional tools such as hoes, crowbars, and hammer. Meanwhile, with machines using tools such as excavators, wheelbarrows, and dompeng. (3) In terms of social life, miners in Nagari Abai are not only carried out by the Abai community, but also come from various regions outside Abai. Mining is also carried out by various levels of society. Keywords: Community, Mining, Gold